The Influence of Tiktok Social Media on Teenagers' Lifestyles - Awanda, Yulia; Harahap, Nursapia; Yoga, Wira; Siregar, Salsa Fadhilah; Ananda, Ridho; Afifah, Nur (AMK : Abdi Masyarakat UIKA, 2024)
TikTok is a social media platform popular among teenagers. The app allows users to create and share short videos that last a maximum of 15 seconds. TikTok has become an important part of teenagers' lives and has impacted their lifestyles in various ways. This study aims to examine the influence of TikTok on teenagers' lifestyles. This research was conducted using a survey method on 100 teenagers in Indonesia. The results showed that TikTok has a positive and negative influence on teenagers' lifestyles. The method used is a survey method with the technique of distributing questionnaires to 100 teenage TikTok users. The results showed that the use of TikTok had a significant effect on teenagers' lifestyles, especially in terms of clothing models, favorite foods and drinks, hobbies and recreational activities, and the use of cosmetics and skincare. The more intensively teenagers use TikTok, the more likely their lifestyles are influenced by the content in TikTok.